Flexible Employment, Flexible Eating and Health Risks - Dixon, Jane; Wodman, Dan; Strazdins, Lyndall; Banwell, Cathy; Broom, Dorothy; Burgess, John (Routledge, 2014)
Over the last 30 years, the risks to public health from working conditions have subtly shifted in line with new economic regimes, notably the shift towards contractualist, individualised market driven and ‘flexible’ regulation of employment associated with the neo-liberal project. Yet, the resulting transformation in temporal schedules has occurred without due consideration of potential health impacts. We contend that contemporary employment policies pose a threat to public health because of their impact on how time is valued, used and experienced. In particular, time matters for earning an income and for basic health behaviours, like healthy eating. The sociological theory of timescapes is used to interpret a qualitative study of food consumption and labour market engagement practices among three generations of Australians. We find that wide variability in individual employment schedules is accompanied by desynchronised social lives and less healthy eating practices. The research leads us to theorise that employment regimes that are flexible for employers require workers to live flexible or fluid cultural lives, disembedded from the temporal structure of previous social rituals, whether culinary, familial or friendship. The health consequences of this requirement remain unrecognised by policy-makers.